PENGARUH PERAN INTERNAL AUDIT, PEMAHAMAN TENTANG PP NO 71 TAHUN 2010, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PENGAWASAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN - Maya Sari Tarigan (AKUNTANSI DEWANTARA, 2019)
This study aims to determine the effect of the role of internal audit, understanding of accounting regulations, utilization of information technology, and supervision of regional finance on the quality of the Yogyakarta City Government's financial reports.     The research is causal research. The data sources used are primary data obtained from questionnaires with a 5-point Likert scale. The questionnaire was 50 respondents and used a purposive sampling method. The data used is in the form of primary data using a questionnaire from a modified previous study. Validity and reliability analysis is used to analyze data.     The results of this study indicate that the role of internal audit does not affect the quality of financial statements, understanding of accounting does not affect the quality of financial statements, the use of information technology has a positive effect on the quality of financial statements, and supervision of regional finance has a positive effect on the quality of financial statements.Keywords: Role of Internal Audit, Understanding of Accounting Regulations, Utilization of Information Technology, Regional Financial Supervision, and Quality of Financial Statements.